Clinical Observation of External Lumbar CSF Drainage Treatment on Intraventricular Hemorrhage - Jian LIN; Maohui LIN; Shuiyuan LIU; Shengze LIU (康复学报)
Objective:To assess the clinical effect of external lumbar CSF drainage treatment on intraventricular hemorrhage.Methods:A retrospective review was conducted for 46 patients with intraventricular hemorrhage from June 2012 to June 2015. They were divided into observation group and control group depending on different treatment plans. Twenty-five patients in the observation group underwent lumbar CSF drainage treatment by Medtronic EDMS external lumbar CSF drainage system, with the method of controlling the flow of CSF of seven days, 120-200 mL per day divided into 3-4 times. Twenty-one patients in the control group did not accept lumbar CSF drainage treatment.Results:Observation group did not develop intracranial infection, the average hospitalized days for 14 days, CT showed all the hematoma were completely absorbed, only three patients appeared hydrocephalus but cured with ventriculo-peritoneal shunt. The average hospitalized days of control group were 29.5 days, all the hematoma were completely absorbed showed by CT, among eight patients appeared hydrocephalus but cured with ventriculo-peritoneal shunt.Conclusion:The patients with intraventricular hemorrhage whom underwent lumbar CSF drainage treatment could improve the clinical treatment effect by reducing incidence rate of hydrocephalus and then shortening hospitalized days.